WOMEN AND PRACTICAL POLITICS IN RIAU PROVINCE - Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
The number of women members of the Regional People's Legislative Assembly for Riau Province has decreased from 18 people (27.69%) in the 2014-2019 period to 12 people (18.46%) in the 2019-2024 period. Even though the number of female voters was 49.19% of the total voters in Riau Province. The purpose of this research is to find out what are the factors that influence women's choices in elections, legislative elections and local elections? This study uses the method of literature study and participatory observation. The results of the study show that female voters do not know the candidate to be elected. Something that is rather difficult for a candidate to be elected if they are not known by voters. The existence of ideological differences is also a barrier for women not to vote for candidates. Men are more suitable to be leaders than women, and this is still a perception for women voters. Women voters' doubts about the religious observance of the candidate to be elected. The door to door system (DDS) strategy for introducing legislative candidates and regional head candidates can be carried out by the winning team (success team), absorbing aspirations and conveying the program to be carried out. Prospective leaders must avoid engaging in money politics and distributing goods in order to get votes. Prospective leaders should show the work and achievements that have been made to the community as proof that they have previously assisted the community in various development activities and programs including women's empowerment activities.